COGNITIVE PROCESS IN TRANSLATION - Ababakirova Marjona Sherzodbek qizi (Galaxy International Interdisciplinary Research Journal, 2024)
This paper explores the sophisticated mental mechanisms that underpin the difficult translation task. It explores how translators use cognitive mechanisms to negotiate linguistic variation, make conclusions, and generate accurate and fluent translations, drawing on findings from neurolinguistics, psycholinguistics, and cognitive psychology. This paper clarifies the cognitive complexities associated with translating tasks from a multidisciplinary lens.